2017
DOI: 10.1371/journal.pone.0183963
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-led telephone-based follow-up of secondary prevention after acute coronary syndrome: One-year results from the randomized controlled NAILED-ACS trial

Abstract: BackgroundSecondary prevention after acute coronary syndrome (ACS) could reduce morbidity and mortality, but guideline targets are seldom reached. We hypothesized that nurse-led telephone-based intervention would increase adherence.MethodsThe NAILED ACS trial is a prospective, controlled, randomized trial. Patients admitted for ACS at Östersund hospital, Sweden, were randomized to usual follow-up by a general practitioner or a nurse-led intervention. The intervention comprised telephone follow-up after 1 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 23 publications
1
31
1
1
Order By: Relevance
“…In total, 11 studies about lipid changes , 11 studies about blood pressure , eight studies about smoking cessation , 13 studies about physical activity , eight studies about medication adherence and four studies about waist circumference were eventually included (summary of study characteristics) (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, 11 studies about lipid changes , 11 studies about blood pressure , eight studies about smoking cessation , 13 studies about physical activity , eight studies about medication adherence and four studies about waist circumference were eventually included (summary of study characteristics) (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies were published between 2015 and 2017, and ten studies between 2003 and 2014. Four studies were conducted in Australia , four in the United States , three in Canada , two each in New Zealand , Sweden and Norway , and one in each of the following countries: Belgium , Italy , Malaysia , Netherlands , Germany , Korea and Iceland .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Another study also confirmed that a nurse-led, telephone-based secondary prevention programme was significantly more efficient at improving low-density lipoprotein cholesterol levels and diastolic blood pressure than usual care. 19 Marcos-Forniol et al 20 showed that the implementation of a secondary prevention programme in elderly patients was effective in achieving risk factor control goals in patients older than 70 years of age. 20 We conclude that secondary prevention is crucial in patients with cardiovascular disease.…”
mentioning
confidence: 99%